Recent advances in the synthesis of aromatic nitro compounds - Yan, Guobing; Yang, Minghua (Organic & biomolecular chemistry, 2013)
Aromatic nitro compounds are important intermediates in synthetic organic chemistry as well as in the chemical industry. Numerous useful methods for their preparation have been developed in recent years. In this review, recent advances in the synthesis of aromatic nitro compounds are summarized, including the nitration of aromatic hydrocarbons, aryl boronic acids, aryl halides and pseudohalides, aryl carboxylic acids and the oxidation of aryl primary amines and azides. Their mechanisms are discussed. Recent advances in the synthesis of aromatic nitro compounds are summarized, including the nitration of aromatic hydrocarbons, aryl boronic acids, aryl halides and pseudohalides, aryl carboxylic acids and the oxidation of aryl primary amines and azides. Their mechanisms are discussed.